Toxicity of extended adjuvant endocrine with aromatase inhibitors in patients with postmenopausal breast cancer: A Systemtic review and Meta-analysis. (December 2020) - Zhao, Fuxing; Ren, Dengfeng; Shen, Guoshuang; Ahmad, Raees; Dong, Li; Du, Feng; Zhao, Jiuda
Graphical abstract: Abstract: Background: Extended endocrine therapy (EET) with aromatase inhibitors (AIs) therapy can further reduce the risk of recurrence in breast cancer patients. But the conclusion that whether EET with AIs increases the risk of some side effects compared with nonextended endocrine therapy (NEET) is still controversial and not exhaustive. Methods: We searched for Randomized controlled trials (RCT) trials published in EMBASE and PubMed between March 2008 and December 2019. Studies comparing the side effects of adjuvant EET with those of NEET were included. The objective was to determine whether EET with AIs increases the risk of side effects compared with NEET. Results: Overall, 11 trials comprising 24, 187 participants were identified. EET with AIs increased the risk of cardiotoxicity [odds ratio (OR) 1.19, 95 % confidence interval (CI) 1.04–1.36; P < 0.05; 438 vs 423], bone pain (OR 1.18, 95 % CI 1.02–1.36; P < 0.05; 446 vs 404), osteoporosis (OR 1.53, 95 % CI 1.35–1.72; P < 0.05; 866 vs 641), fractures (OR 1.33, 95 % CI 1.18–1.50; P < 0.05; 596 vs 438), arthralgia (OR 1.27, 95 % CI 1.19–1.36; P < 0.05; 2404 vs 2060), myalgia (OR 1.29, 95 % CI 1.16–1.43; P < 0.05; 960 vs 776), and hot flashes (OR 1.40, 95 % CI 1.15–1.69; P < 0.05; 2418 vs 2174) and was associated with opposite risk of vaginal bleeding (OR 0.74, 95 % CI 0.59–0.92; P < 0.05; 148 vs 197). However, the extended therapy did not increase the risk of hypertension (OR 1.03, 95 % CI 0.80–1.33; P = 0.80; 364 vs 353), hypercholesterolemia (OR 1.03, 95 % CI 0.91–1.16; P = 0.62; 643 vs 627), vaginal dryness (OR 1.19, 95 % CI 1.00–1.42; P = 0.05; 294 vs 257), fatigue (OR 1.20, 95 % CI 0.96–1.50; P = 0.12; 1501 vs 1462), dizziness (OR 1.04, 95 % CI 0.92–1.17; P = 0.55; 614 vs 595), headaches (OR 1.06, 95 % CI 0.95–1.18; P = 0.30; 885 vs 848), constipation (OR 0.91, 95 % CI 0.79–1.04; P = 0.15; 480 vs 522), nausea (OR 1.83, 95 % CI 0.49–6.83; P =0.37; 340 vs 325), and dyspnea (OR 0.96, 95 % CI 0.82–1.13; P = 0.64; 340 vs 351). The risk of grade ≥ 3 hot flashes increased following extended endocrine therapy (OR 2.01, 95 % CI 1.23–3.29; P < 0.05; 47 vs 23). We observed no evidence for a difference in the risk of grade ≥3 fatigue, arthralgia, myalgia, bone pain, osteoporosis, fractures, hypertension, and headache between both endocrine therapies. Secondary outcomes shows that after receive EET with AIs, patients can benefit from the control of the local recurrence, distant recurrence, contralateral breast cancer, and second cancers. Conclusions: Compared with NEET, EET with AIs significantly increased the risk of cardiotoxicity, bone pain, osteoporosis, fractures, hot flashes, arthralgia, myalgia, and grade ≥3 hot flashes, and EET with AIs can reduced the risks of local recurrence, distant recurrence, contralateral breast cancer, and second cancers. These findings offer an important guide for clinicians and patients.